Workshop pendekatan mic untuk memfasilitasi kemampuan pemecahan masalah dan psychological well being siswa bagi orangtua siswa SD 1 Susukan Kec. Cipicung Kab. Kuningan - Fatimah Zahrah, Riza; Sidik, Geri Syahril; Febriani, Winarti Dwi; Mulyani, Hanifah; Anugrahayu, Alga; Hilman, Hilman (IKIP SILIWANGI, 2025)
SD Negeri 1 Susukan, located in Cipicung sub-district, Kuningan district, is an elementary school in Cipicung sub-district that still has B accreditation. SD Negeri 1 Susukan is located in Cipicung sub-district which has environmental conditions that are included in remote areas. The access to get there is quite far and the terrain is rather difficult, the road is damaged and has many holes. The background to parents' low understanding of the importance of parenting is the low level of parental education and the lack of parenting activities at SDN 1 Susukan. The importance of parents' understanding is not only about cognitive development (students' mathematical problem solving ability) but also students' psychological well being that needs to be considered by teachers and parents. The solution offered is to conduct workshop activities for parents regarding the importance of the learning process, especially in students' mathematical problem solving ability and workshops for parents regarding the importance of students' psychological well beingin the learning process in elementary school. The implementation method used in this PKM activity includes the method of technology transfer and continuous mentoring from the Implementation Team to partners in stages for 4-5 meetings. The results of this service are an increase in participants' understanding of the importance of psychological well being to facilitate problem solving skills by 0.40 with a moderate category.